Influence of interfacial transition zone on engineering properties of the concrete manufactured with recycled ceramic aggregate - Medina, César; Zhu, Wenzhong; Howind, Torsten; de Rojas, María Isabel Sánchez; Frías, Moisés (Journal of Civil Engineering and Management, 2014)
The influence of the local micro-properties of the interfacial transition zone (ITZ) on macro-properties on the behaviour concretes is studied for recycled concretes made with 20% and 25% recycled ceramic aggregate from sanitary ware waste. This study carried out using nanoindentation and SEM technique aims to explore interface thickness and variations in its elastic modulus. The results show that the minimum and mean values of the elastic modulus and the ITZ thickness impact concrete mechanical and elastic properties to different degrees. Finally, that nanoindentation provides an indispensable tool for studying and assessing the effect of new materials (e.g. recycled aggregates) on the micromechanical properties of the interfacial transition zone (ITZ) and its effect on engineering properties (compressive and splitting tensile strength and modulus of elasticity) of these new concretes.